2004
DOI: 10.1038/sj.onc.1207416
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and TGFβ signalling cooperate to maintain a mesenchymal phenotype after FosER-induced epithelial to mesenchymal transition

Abstract: Several signalling pathways contribute to the regulation of epithelial to mesenchymal transition (EMT), either during developmentally regulated processes or in cancer progression and metastasis. Induction of EMT in fully polarized mouse mammary epithelial cells (EpH4) by an inducible cfos estrogen receptor (FosER) oncoprotein involves loss of E-cadherin expression, nuclear translocation of b-catenin, and autocrine production of TGFb. Reporter assays demonstrate that both b-catenin/LEF-TCF-and TGFbSmad-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 52 publications
2
100
0
1
Order By: Relevance
“…Loss or attenuation of epithelial polarity is the hallmark of EMT, which occurs in development and cancer progression [55]. The junction proteins localize differently in proliferating (mesenchyma) or TJ-containing (epithelia) cells, which may be reminiscent of their separate functions [56]. It is also widely appreciated that the specialized structures at cell contacts (such as TJs, adherent junctions and desmosomes) are focal points for cell-cell signaling pathways implicated in growth and differentiation, and the different roles of the TJ proteins may be achieved through regulating their variant sub-cellular locations.…”
Section: Intercellular Junctions and Dna Damage Repairmentioning
confidence: 99%
“…Loss or attenuation of epithelial polarity is the hallmark of EMT, which occurs in development and cancer progression [55]. The junction proteins localize differently in proliferating (mesenchyma) or TJ-containing (epithelia) cells, which may be reminiscent of their separate functions [56]. It is also widely appreciated that the specialized structures at cell contacts (such as TJs, adherent junctions and desmosomes) are focal points for cell-cell signaling pathways implicated in growth and differentiation, and the different roles of the TJ proteins may be achieved through regulating their variant sub-cellular locations.…”
Section: Intercellular Junctions and Dna Damage Repairmentioning
confidence: 99%
“…21,22,40 Unlike human breast cancer cells where upstream signalling kinases activation is required, 14,16 ectopic Fra-1 expression was sufficient for EMT and tumorigenesis in EpH4 cells. Moreover, Fra-1 increased TGFβ expression and production, similarly to c-Fos and unlike oncogenic Ras, 43 thus TGFβ treatment was not necessary for EMT in EpFra1 cells. We demonstrated that Fra-1 binds to two regions in the murine tgfb1 promoter containing several AP-1-binding elements.…”
Section: Discussionmentioning
confidence: 89%
“…However, inhibition of TGFβ signalling in EpFra1 cells only partially restored epithelial markers expression, similarly to the situation during Fos-or ERK2-induced EMT. 14,43 Thus, TGFβ signalling is likely insufficient for EMT in the context of ectopic Fra-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The coactivator function of b-catenin is induced by recruitment of the basal transcription machinery (Hecht et al, 1999) and is enhanced by synergistic cooperation with a number of other proteins such as coactivators, (Zhurinsky et al, 2000;Martin et al, 2002;Grueneberg et al, 2003;Wei et al, 2003) or proteins involved in chromatin remodeling and histone modification (Hecht et al, 2000;Miyagishi et al, 2000;Sun et al, 2000;Takemaru and Moon, 2000;Barker et al, 2001). Not surprisingly, mounting evidence indicate that b-catenin is able to cross-talk with a variety of signalling cascades, such as those involving Rac GTPase, forkhead box O transcription factors or transforming growth factor (TGF)b (Eger et al, 2004;Esufali and Bapat, 2004;Chakladar et al, 2005;Essers et al, 2005).…”
mentioning
confidence: 99%